Daughters of the Lake - Webb, Wendy (Wendy K.) (Thorndike, Maine Center Point Large Print, 2019)
"After the end of her marriage, Kate Granger retreated to her parents home on Lake Superior to pull herself together--only to discover the body of a murdered woman washed into the shallows. As the drowned woman reaches out from the grave, Kate reaches back, coming together, if only in dreams, to right the sinister wrongs of the past"- -
Keywords: Cold cases (Criminal investigation) -- Fiction; Divorced women -- Fiction; Homecoming -- Fiction; Family secrets -- Fiction; Dreams -- Fiction; Superior, Lake -- Fiction; Gothic fiction; Paranormal fiction; Occult fiction